2016
DOI: 10.1177/0890117116671537
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Undiagnosed Hyperlipidemia: Do Work Site Screening Programs Work?

Abstract: Workplace health screenings in an insured population were associated with a subsequent increase in physician visits and prescriptions for hyperlipidemia. After 1 year, significant improvements in total cholesterol and LDL levels were observed among individuals who screened positive for hyperlipidemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…We excluded 89 articles which were duplicate studies (n=1); performed before the year 2000 (n=9); had absence of full text or lack of sufficient data for extraction (n=22); had the presence of known diabetes, pre-diabetes or CVD (n=44); or target population whose subjects reported family history of diabetes, pre-diabetes or elevated BMI (n=13). Finally, we included 38 studies from 33 articles in the present systematic review 27–59…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We excluded 89 articles which were duplicate studies (n=1); performed before the year 2000 (n=9); had absence of full text or lack of sufficient data for extraction (n=22); had the presence of known diabetes, pre-diabetes or CVD (n=44); or target population whose subjects reported family history of diabetes, pre-diabetes or elevated BMI (n=13). Finally, we included 38 studies from 33 articles in the present systematic review 27–59…”
Section: Resultsmentioning
confidence: 99%
“…A total of four studies offered lipid screening33 34 51 57: one cross-sectional screening survey was covered by research funding,57 one study was workplace-based screening and insured by employers33 and the other two studies were for national screening programmes supported by government organisations 34 51. Only one study was from a developed country33 (table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When WMLs result from hypoxic-ischemic brain lesions and lead to cognitive impairment, this complex disorder is characterized as SAE [ 17 ]. Individuals were considered to have hyperlipidemia at screening if they had a total cholesterol level of more than 6.2 mmol/L (240 mg/dL), serum triglycerides concentrations more than 2.3 mmol/L (200 mg/dL), serum LDL-C concentrations more than 4.1 mmol/L (160 mg/dL) or serum HDL-C concentrations less than 1.0 mmol/L (40 mg/dL) [ 43 47 ]. Hypoglycemia was defined in subjects with a plasma glucose of ≤3.9mmol/L and/or self-reported probable hypoglycemic symptoms [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…Most updated literatures showed that in 2019 there are 50.1% (231.9 million) of diabetes patients still undiagnosed worldwide 5 . A large proportion of cases with hypertension 6 and hyperlipidemia 7 are also unware of their condition, particularly in low and middle income countries 8 .…”
mentioning
confidence: 99%